2019
DOI: 10.3390/ijms20061514
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 50 Neurodegenerative Genes in Clinically Diagnosed Early-Onset Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD), Parkinson’s disease (PD), frontotemporal dementia (FTD), amyotrophic lateral sclerosis (ALS), Huntington’s disease (HD), and prion diseases have a certain degree of clinical, pathological, and molecular overlapping. Previous studies revealed that many causative mutations in AD, PD, and FTD/ALS genes could be found in clinical familial and sporadic AD. To further elucidate the missing heritability in early-onset Alzheimer’s disease (EOAD), we genetically characterized a Thai EOAD cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 61 publications
1
59
0
Order By: Relevance
“…Recent studies identified that rare variants in several GWAS loci of AD were segregated in LOAD families and may confer risk of AD. [10][11][12] Pathogenic mutations of FTD and PD related genes were presented in dementia patients or families that formerly diagnosed of AD, 19,20 suggesting that rare, pathogenic variants of neurodegenerative genes other than APP, PSEN1 and PSEN2 may account for etiology of the remaining AD families. In this study, we analyzed the association of rare variants in neurodegenerative diseases genes as well as APOE in a Chinese FAD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified that rare variants in several GWAS loci of AD were segregated in LOAD families and may confer risk of AD. [10][11][12] Pathogenic mutations of FTD and PD related genes were presented in dementia patients or families that formerly diagnosed of AD, 19,20 suggesting that rare, pathogenic variants of neurodegenerative genes other than APP, PSEN1 and PSEN2 may account for etiology of the remaining AD families. In this study, we analyzed the association of rare variants in neurodegenerative diseases genes as well as APOE in a Chinese FAD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Complex genetic investigation by next generation sequencing (NGS) was performed on the proband patient. Targeted NGS approaches were carried out with a panel of 50 causative and risk factor genes in neurodegenerative diseases by Theragen Etex Bio Institute on an IonProton device [20]. The standard Sanger sequencing verified the NGS data by BioNeer Inc. (http://eng.bioneer.com/home.aspx, Bioneer Inc., Daejeon, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Additional symptoms, such as Parkinsonism, epilepsy, and language and behavioral impairment may also be prominent in EOAD [17]. Interestingly, de novo cases of AD mutations were also reported without prior family history or any affected family members [2,[18][19][20]. In this study, a pathogenic PSEN1 p.Glu184Gly (g.14:73659354 A>G; c.551A>G; p.E184G) mutation was discovered in an EOAD patient from a Thai family, noted as the first case in Asia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria were lack of cooperation, life-threatening diseases, psychotropic therapies, history of disabling cardiovascular diseases, ictus or other potential life-threatening conditions, myocardial infarction, transient ischemic attacks or stroke, familiarity of neurodegenerative processes, or in advanced stages of disease. Patients with a history or family history of neurodegenerative diseases were excluded to avoid the contribution of early-onset diseases, which typically have a genetic etiology (Giau et al, 2019). Additionally, adults with hearing aids or cochlear implants were also excluded to avoid interference of digital devices with the acoustic properties of the auditory stimuli, which could significantly modify the SNR (Gallo and Castiglione, 2019).…”
Section: Methodsmentioning
confidence: 99%